Socioeconomic inequalities and their influence on Kichwa bilingual education at the secondary school level, Ecuador - Vizuete Montero, Marco Omar (2024)
Objective. To analyze and understand the implication of socioeconomic inequality in Kichwa bilingual education. Method. A quantitative approach with a non- experimental and descriptive design was conducted. The population and sample consisted of 108 students and 13 teachers from the Intercultural Bilingual Educational Unit "Oriente Ecuatoriano." The data collection instrument was a questionnaire with structured questions about socioeconomic inequalities and academic performance. Data analysis was conducted in stages: questionnaire delivery to teachers, detailed explanation of survey completion instructions, and was developed through statistical tests. Results. The results confirm the existence of socioeconomic dificulties with academic performance, which is supported by a moderate correlation (r = 0.5). Within the academic performance grades, an average performance of 3.5 and a strong correlation (r = 0.7) are achieved due to the constant participation of students and teachers. Meanwhile, teachers deduce that there are socioeconomic inequalities among students and that these influence different educational experiences. In relation to academic performance, a moderate correlation (r = 0.5) was determined between academic growth and socioeconomic conditions. Conclusions. There is a need to implement sensitive pedagogical approaches and programs that help achieve professional development.